COVID-19 impact in radiotherapy practice in an oncology hub: a screenshot from Lombardy, Italy. Issue 6 (December 2021) - Corrao, Giulia; Bergamaschi, Luca; Zaffaroni, Mattia; Sarra Fiore, Massimo; Bufi, Giammaria; Leonardi, Maria Cristina; Lazzari, Roberta; Alterio, Daniela; Cattani, Federica; Pravettoni, Gabriella; Mastrilli, Fabrizio; Orecchia, Roberto; et al.
Objective: During 2020, medical clinical activities were dramatically modified by the coronavirus disease 2019 (COVID-19) emergency. We aim to evaluate the impact of COVID-19 on radiotherapy (RT) practice in a hub cancer center. Methods: Retrospective data collection of patients with suspected COVID-19 infection, identified by pathognomonic symptoms feedback at triage realized at the entrance to RT division. Inclusion criteria were diagnosis of oncologic disease, COVID-19–related symptoms, and signed written informed consent. Results: Between 1 March and 30 June 2020, 1, 006 patients accessed our RT division for RT simulation or treatment. Forty-four patients matched inclusion criteria (4.4% of all patients): 29 women and 15 men. Seventeen patients had metastatic disease. Twenty-one patients reported fever, 6 presented dyspnea, 4 complained of ageusia and anosmia, and 3 developed conjunctivitis. Thirty-six patients underwent nasal swab, with 7 positive results. From our cohort, 4 cases of pneumonia were diagnosed with computed tomography scan imaging: 3 were related to COVID-19 infection, while the fourth was evaluated as an RT adverse event. From the entire series, 4 patients died: 3 during hospitalization in intensive care unit of complications of COVID-19 and 1 of other causes neither COVID-19 nor cancer-related. Conclusions: Cancer hub allows for safe RT practice continuation while minimizing the spread of contagion in this frail patient population. A challenge for the future will be to understand pandemic consequences in cancer natural history and manage its clinical impact.